2021
DOI: 10.1039/d1ra04099e
|View full text |Cite
|
Sign up to set email alerts
|

Applications of aryl-sulfinamides in the synthesis of N-heterocycles

Abstract: The review comprehends the usage of arylsulfinamides for the construction of diverse N-heterocycles like piperidines, pyrrolidines, aziridines, and their fused derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The power of the sulfinyl group in exerting exceptional selectivity in the nucleophilic addition reactions and the ease of deprotection of the sulfinyl group led to these reagents being widely used in the stereoselective synthesis of several nitrogen-containing molecules of therapeutic significance. The groups of Davis and Ellman pioneered the exploration of the addition of various nucleophiles to sulfinimines . We have recently shown that the addition of arylmethyl ketones to sulfinimines proceeds with excellent diastereoselectivity .…”
Section: Introductionmentioning
confidence: 99%
“…The power of the sulfinyl group in exerting exceptional selectivity in the nucleophilic addition reactions and the ease of deprotection of the sulfinyl group led to these reagents being widely used in the stereoselective synthesis of several nitrogen-containing molecules of therapeutic significance. The groups of Davis and Ellman pioneered the exploration of the addition of various nucleophiles to sulfinimines . We have recently shown that the addition of arylmethyl ketones to sulfinimines proceeds with excellent diastereoselectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews surveyed an aspect of the synthetic protocols accord The huge interest in this structural motif has led to great efforts in developing novel and efficient synthetic strategies for the asymmetric construction of substituted chiral pyrrolidines. Some reviews surveyed an aspect of the synthetic protocols according to a peculiar focus, usually related to a specific chemical transformation: asymmetric syntheses of pyrrolidines exploiting organocatalysis [14], asymmetric [3 + 2]-cycloadditions involving azomethine ylides [15], catalytic asymmetric 1,3-dipolar cycloadditions [16], aryl-sulfinamides in the synthesis of N-heterocycles [17], synthesis of N-phosphorylated pyrrolidines [18], annulation strategies for the construction of multisubstituted pyrrolidines as natural products [19], or palladium-catalyzed alkene aminoarylation reactions [20]. Conversely, in this review, we focus on the advances achieved in the last 15 years (between 2008 and 2022) in the asymmetric synthesis of novel chiral pyrrolidine-based organocata-lysts, including all of the proposed synthetic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfinamides constitute a privileged structural motif in pharmaceuticals and natural products . They also serve as versatile synthetic blocks, chiral auxiliaries as represented by N - tert -butyl sulfinamides (Ellman’s sulfinamide), ligands, and catalysts in organic synthesis . Sulfoxides are also typical structural units in natural products, drugs, and herbicides and play a key role in organic synthesis, being widely applied as synthetic intermediates, chiral auxiliaries, ligands, and catalysts. , Sulfinamides have been synthesized by the reactions of preformed sulfinyl chlorides with amines, oxidative couplings of thiols with amines, reductive couplings of sulfonyl chlorides with amines, and oxidation of sulfenamides .…”
mentioning
confidence: 99%